THE ESSENCE AND FEATURES OF THE FORMATION OF EXPORT POTENTIAL AS AN ELEMENT OF ENTERPRISE DEVELOPMENT - MAZUR, Dmytro; MAZUR, Oleksandr; MAZUR, Halyna; KOVBIY, Antonina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The authors of the article considered the issue of the formation of export potential as an element of enterprise development, and its essence and enterprise. The essence and peculiarities of the formation of expert potential are determined in this study. The export potential, which is formed from two types of potential: internal and external, is analyzed. The directions for the formation of export potential have been determined: industrial, financial, personnel and market. In this study, the factors that affect the export potential of enterprises, which form the center of formation and production of export potential - technical, social-cultural, political-legal, economic, natural-climatic are considered. This article shows the definition of export potential, and how it is used to determine the degree of growth of an enterprise in space and time, with the help of an economic group. Several periods of the company’s growth are considered. Aspects of the enterprise’s competitiveness, which gives an opportunity to increase the existing resources and the direction of the export potential for the development of the enterprise, are outlined in the study. Defined. That the export potential is the only one of the main factors that qualifies the success of the enterprise in the modern conditions of the foreign market. This article examines the fact that the higher the expert potential, the more competitive and attractive the enterprise becomes. The understanding of the formation of expert potential as an element of enterprise growth, its essence and elements is defined. The authors revealed the relevance of the research, determined the purpose and tasks that were given when writing this article.